Not everyone gets a trophy : how to bring out the best in young talent - Tulgan, Bruce (John Wiley & Sons, Inc., 2023)
"Based on more than a decade of research, Not Everyone Gets a Trophy reframes Millennials at a time when many employers are struggling to engage, develop, and retain them. Not Everyone Gets a Trophy, 3rd Edition provides proven, step-by-step best practices for getting Millennials onboard and up-to-speed?giving them the context they lack, teaching them how to manage themselves and how to be managed, and turning the very best into new leaders. This book is the essential guide for winning the talent wars and managing Millennials. This new revised and updated edition includes: New focus on all millennials, which include Generations X, Y, and Z New preface about the incredible generational shift under way in the workforce now and the critical nature of this issue now Updated case studies and examples New research on first-wave and second-wave of the Millennials"--